TOR Inhibitors Synergistically Suppress the Growth and Development of Phytophthora infestans, a Highly Destructive Pathogenic Oomycete - Zhang, Shumin; Khalid, A. Rehman; Guo, Dongmei; Zhang, Jingping; Xiong, Fangjie; Ren, Maozhi (Frontiers in Microbiology, 2021)
Pathogenic oomycetes infect a wide variety of organisms ranging from plants and animals to humans, causing economic losses in agriculture, aquaculture and human health. The target of rapamycin (TOR) is well known as a key gene in eukaryotes that controls cell growth, survival and development. However, its function in controlling pathogenic oomycetes is unclear. Here, Phytophthora infestans, one of most famous pathogenic oomycetes, is used as the model system to explore the application of the TOR signaling pathway in controlling pathogenic oomycetes. In this study, we found that the TOR signaling pathway is conserved in Phytophthora infestans. TOR inhibitors, including rapamycin (RAP), AZD8055 (AZD), KU-0063794 (KU) and Torin1, obviously inhibit Phytophthora infestans, and AZD shows the best inhibitory effects on P. infestans. Importantly, compared with a combination of RAP+KU or RAP+Torin1, the co-application of RAP and AZD showed the best synergistic inhibitory effects on P. infestans, resulting in the reduced dosage and increased efficacy of drugs. Transcriptome analysis supports the synergistic phenotype that the combination of RAP and AZD exhibits synergistic effects on genes, functions and pathways related to the TOR signaling pathway. Thus, TOR is an important target for controlling pathogenic oomycetes, and synergism based on the application of TOR inhibitors is an effective and novel method for controlling pathogenic oomycetes.